THE NATIONAL SCHOOL MEAL PROGRAM IN THE MUNICIPALITY OF TUPA AND ITS EFFECTS ON FAMILY FARMING - Lourenzani, Ana Elisa Bressan Smith [UNESP]; Cardoso, Vitoria Aparecida [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2019)
The aim of this study is to identify the effects of income involved with the National School Meal Program (PNAE) on family farming in the municipality of Tupa. While still considered very important for food safety, whereas rebalancing the food supply, family-run farms is now struggling with problems. Conscious of this, the Government has been adopting a series of measures to foster this category; one of which is Law No. 11,947, and establishes that at least 30 % of the total resources forwarded to the National School Meal Program (PNAE) should be destined to the purchase from family farming products. To evaluate the effects of this law in familiar agriculture, 23 family farmers trading directly with (PNAE) NPSFP in Tupa were inter viewed. As a result, it was possible to observe that the program has positive effect in the adoption of technology, and investments in infrastructure, diversification and quantity of production. The survey also showed that, of all problems faced by these producers when participating in the program, we are aware of the main obstacles is the difficulty of reconciling monthly variation in production and demand.
Keywords: Family farming; National School Meal Program; Tupa; School meals; Public policy